Traffic Safety Stickers for the Children with Hearing Impairment - Nur Hasan; Abdul Huda; Henry Prahendiono (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2019)
Children with hearing impairment have the same rights and obligations when in a traffic area. Drivers with hearing impairment must wear identification when in the traffic area. In fact, there are no drivers with hearing impairment who use special identification cards. The purpose of this development is to produce driving safety stickers in traffic for students with hearing impairments and to assist the government in socializing about traffic regulations, especially identification for drivers with hearing impairment. This study uses a research and development (R&D) development model that adapts the steps of the Borg & Gall development model. The results of the development show the level of validity of driving safety stickers for the drivers with hearing impairment are included into very well or suitable to be used. In conclusion, hearing impairment drivers need special identification cards when driving on the highway.